2020
DOI: 10.14740/jh614
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Thrombotic Complications in a Thrombotic Thrombocytopenic Purpura Patient Treated With Caplacizumab

Abstract: Thrombotic thrombocytopenic purpura (TTP) is a rare and unpredictable disease with a high mortality rate (90%) if untreated. It results from systemic microvascular thrombosis and leads to profound thrombocytopenia, hemolytic anemia and organ failure of varying severity. However, macrovascular thrombosis has been described in very rare cases. Caplacizumab has emerged as a promising new drug for the management of TTP. We report the case of a patient with idiopathic refractory TTP treated with caplacizumab who de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In a recently published case report demonstrating a patient with refractory iTTP, both DVT and arterial thrombosis occurred shortly after caplacizumab discontinuation without TTP recurrence [22]. The patient did not receive any antithrombotic agent while on caplacizumab.…”
Section: Thrombotic and Bleeding Events In Ttp Patients Receiving Caplacizumabmentioning
confidence: 93%
“…In a recently published case report demonstrating a patient with refractory iTTP, both DVT and arterial thrombosis occurred shortly after caplacizumab discontinuation without TTP recurrence [22]. The patient did not receive any antithrombotic agent while on caplacizumab.…”
Section: Thrombotic and Bleeding Events In Ttp Patients Receiving Caplacizumabmentioning
confidence: 93%
“…A recent cost-effectiveness analysis showed that over a 5-year period, the projected incremental cost- effectiveness ratio was $1,482,260, which is well over the accepted 2019 US willingness-to-pay threshold of $195,300 ( Goshua et al, 2021 ). Cost aside, caplacizumab will likely provide a benefit for refractory cases, including patients who have failed trials of plasma exchange and immunosuppressive agents, as can already be seen in limited case reports ( Cilla et al, 2020 ; Kaczmarek et al, 2019 ).…”
Section: Implications For Advanced Practitionersmentioning
confidence: 97%